Does organic agriculture lead to better health among poor farmers? An investigation of health expenditure among organic and conventional farmers in Thailand - Sunantar Setboonsarng; Rouselle F. Lavado (Asian Development Bank Institute (ADBI), 2008)
Poverty and health are inextricably linked as the poor are always the first to suffer from degraded soil, water, and environment. For poor farmers in developing countries, inappropriate use of pesticides is known to be a serious problem. To investigate if adoption of organic agriculture leads to better health or lower expenditure on healthcare, a survey was conducted on organic and conventional rice-farming households in North and Northeast Thailand in 2006. The results show that health expenditure of conventional farmers is 56% higher than organic farmers. The burden of health expenditures is also disproportionately borne by the poor with the two poorest quintiles spending approximately 3% of discretionary expenditure on healthcare, compared with only 1.85% for the two richest quintiles. Catastrophic health expenditure is also significantly higher for conventional farmers than organic farmers. Among households with health expenditure exceeding 40% of discretionary expenditure, the percentage is 1.3% for conventional households compared to 0.25% for organic households. Although health outcomes are influenced by factors other than pesticide exposure, the results suggest that organic farmers may be in better health. Results also show that organic farmers have more to spend on other household necessities rather than having to spend more discretionary income on healthcare, implying better welfare. The results suggest that organic agriculture as a development strategy might lead to improved health, one of the foundations to sustainable poverty reduction.
Keywords: I18; I3; Q12; 330